A morphological, anatomical and pollen study of the Erodium malacoides(L.)willd. common species in Tartous governorate - شدود نسرين; عفيفة عيسى (Latakia University Journal -Biological Sciences Series, 2023)
In this research, the morphological study was conducted on the specie Erodium malacoides L., where the different parts of the flower were studied(petals, sepals, stamens and the fruit) which consisted of 5 fruits, The seed is oval in shape and its dimensions are 0.8-1×2.3-2.7 mm, the anatomical study showed that the cross section of the root is circular in shape and the wood and phelum are continuous,and the stem is also circular in shape and the number of vascular bundles is 10, varying in size, the study showed that the pattern of pollen grains is spherical with three germination lines.